PERANCANGAN SISTEM INFORMASI PENDATAAN BARANG PADA PT. SERDANG HULU - Victor Marudut Mulia Siregar; Heru Sugara; Ivana Maretha Siregar (STMIK Mardira Indonesia, Bandung, 2018)
Designing information system for collecting data at PT. Serdang Hulu is done to help simplify data collection and recording data on incoming and outgoing goods at the company. PT. Serdang Hulu which is a subsidiary of PT. Sumatra Sarana Sekar Sakti or what is often referred to as Sumatra Sarana Sekar Sakti Group (SSSS Group) is a company that distributes palm oil. In carrying out their daily activities, data on goods that come in and out at PT. Serdang Hulu is still manually recorded in the book listing incoming and outgoing goods. Recording of incoming and outgoing goods that are carried out manually results in the work of collecting data taking a long time so that it is not efficient in presenting the report and is not effective at work. With the design of the Data Entry and Exit Data Collection System, recording data on incoming and outgoing goods at PT. Serdang Hulu is more effective and efficient so it is easier and faster in presenting reports. Keyword : Systems, information, records, goodsDOI:10.5281/zenodo.3232903